Increasing the Accuracy in Determining the Basis Foundation Compressibility - Kostochka, Nataliia; Miroshnychenko, Iryna; Nalyvayko, Oleksandr (International Journal of Engineering and Technology, 2018)
The disadvantages of the standard soil deformation characteristics are analyzed. Impact of different factors on the determination accuracy of soil characteristics is estimated. Devices to determine soil deformation parameters in the conditions of one axial compression aimed at increase in reliability of the soil compressibility evaluation results are improved; the mentioned improving eliminate disadvantages of the compression device that is absence of the soil sample lateral expansion and friction with ring walls decreasing the soil sample lateral expansion and reduces real soil compressibility. Results of the soil tests in the standard and improving device are compared with each other. Soil compressibility index is based. Such index represents the relative change in the soil sample porosity coefficient during the compression tests. There is increase in prediction accuracy of the building soil foundations settlements. To increase prediction accuracy soil compressibility index and account of the influence of pressure on the soil deformation parameters and soil porosity changing from the compressible thickness depth are used. Statistical analyze of the random variables of the soil base settlements, which are predicted by the both methodic are made.Â Â